C−H Direct Arylated 6H‐Indolo[2, 3‐b]quinoxaline Derivative as a Thickness‐Dependent Hole‐Injection Layer. Issue 8 (22nd March 2017) - Dong, Dai; Fang, Da; Li, Hairong; Zhu, Caixia; Zhao, Xianghua; Li, Jiewei; Jin, Lingzhi; Xie, Linghai; Chen, Lin; Zhao, Jianfeng; Zhang, Hongmei; Huang, Wei
Abstract: A novel perfluoro‐1, 4‐phenylenyl 6 H ‐indolo[2, 3‐ b ]quinoxaline derivative (TFBIQ ) was designed and synthesized by using a C−H direct arylation method. The optoelectrical properties of the obtainedTFBIQ were fully characterized by UV/Vis spectroscopy, photoluminescence spectroscopy, cyclic voltammetry, and a group of Alq3 ‐based green organic light‐emitting diodes (OLEDs). Device A, which used 0.5 nm‐thickTFBIQ as the interfacial modification layer, exhibited the five best advantages of device performance including a minimum turn‐on voltage as low as 3.1 V, a maximum luminescence intensity as high as 26564 cd m −2, a highest current density value of 348.9 mA cm −2 at a voltage of 11 V, the smallest efficiency roll‐off, as well as the greatest power efficiency of 1.46 lm W −1 relative to all of the other tested devices with thickerTFBIQ and also 10 nm‐thick MoO3 as hole‐injection layers (HILs). As a promising candidate for an organic HIL material, the as‐preparedTFBIQ exhibited a strong thickness effect on the performance of corresponding OLEDs. Furthermore, the theoretical calculated vertical ionization potential of the fluorinatedTFBIQ suggests better anti‐oxidation stability than that of the non‐fluorinated structure. Abstract : The hole truth : A symmetrical 6 H ‐indolo[2, 3‐ b ]quinoxaline derivative containing a bridged tetrafluoro‐ p ‐phenylene is as an effective hole‐injection layer material in organic light‐emitting devices (see figure).